Análise de sistemas construtivos para execução de edificação vertical de programa habitacional - Pretto, Emanuele Furlan (2018)
In this work we seek to identify an appropriate building system for a multi-residential urban vertical construction of a government housing program, we focused our analysis based in some building process as: structural (pillars, beams and slabs), locks (walls, divisors and roof) and coatings (walls, lining and floor). We did a literature review using the Pro-Know-C method to identify the most relevant papers and alignment with the theme, based on this review and our practical experience we identified systems that can result in a greater productivity in the building site, adequate material logistics and best cost-effective in the final product. From this, we elaborate a questionnaire for the technical team of a construction company from the Foz do Iguaçu, West of Parana, which has 8 (eight) professionals, to identify their choices around the main building systems. In a second moment, we did a brainstorming with this team to identify strengths and weaknesses of the chosen systems and, finally, to define the appropriate system to be applied. From the results of the research we conclude that we have the opportunity to develop new building systems and technologies, however it is necessary to overcome logistical difficulties and professional training, always guiding for greater productivity and quality final product. In addition, the identification of a building system adequate for a multi-residential urban vertical construction gave the basis for the complementary projects, with the assurance that the building system proposed in this study was the best choice of the moment lived by the technical team and the construction company, taking into account the region that the company it is located.